Integrative analysis in toxicological assessment of the insecticide Malathion in Allium cepa L. system - Ghisi,N. C. (2023)
Abstract For many centuries human populations have been suffering and trying to fight with disease-bearing mosquitoes. Emerging and reemerging diseases such as Dengue, Zika, and Chikungunya affect billions of people around the world and recently has been appealing to control with chemical pesticides. Malathion (MT) is one of the main pesticides used against mosquitoes, the vectors of these diseases. This study aimed to assess cytotoxicity and mutagenicity of the malathion for the bioindicator Allium cepa L. using a multivariate and integrative approach. Moreover, an appendix table was compiled with all available literature of insecticides assessed by the Allium cepa system to support our discussion. Exposures during 48h to 0.5 mg mL-1 and 1.0 mg mL-1 MT were compared to the negative control (distilled water) and positive control (MMS solution at 10 mg L-1). The presence of chromosomal aberrations, micronuclei frequency, and mitotic index abnormalities was evaluated. Anaphase bridges were the alterations with higher incidence and presented a significantly elevated rate in the concentration of 0.5 mg mL-1, including when compared to the positive control. The integrative discriminant analysis summarizes that MT in assessed concentrations presented effects like the positive control, corroborating its potential of toxicity to DNA. Therefore, it is concluded that MT in its pure composition and in realistic concentrations used, has genotoxic potential in the biological assessment of A. cepa cells. The multivariate integrative analysis was fundamental to show a whole response of all data, providing a global view of the effect of MT on DNA.